2022
DOI: 10.3390/chemistry4030045
|View full text |Cite
|
Sign up to set email alerts
|

hERG Blockade Prediction by Combining Site Identification by Ligand Competitive Saturation and Physicochemical Properties

Abstract: The human ether-a-go-go-related gene (hERG) potassium channel is a well-known contributor to drug-induced cardiotoxicity and therefore is an extremely important target when performing safety assessments of drug candidates. Ligand-based approaches in connection with quantitative structure active relationships (QSAR) analyses have been developed to predict hERG toxicity. The availability of the recent published cryogenic electron microscopy (cryo-EM) structure for the hERG channel opened the prospect of using st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…An important feature of the SILCS methodology is the use of GCMC sampling allowing for improved sampling of water and solutes throughout the simulation systems over that, which can occur versus the use of MD alone along with the ability to sample very deep and fully occluded pockets on the interior of proteins. To further improve the GCMC acceptance rates for solutes, we previously developed the oscillating μ ex GCMC approach, 8 which has been used successfully in a number of studies 43 . Accordingly, taking advantage of the improved sampling and computational efficiency associated with the GPU implementation described above, the oscillating μ ex GCMC methodology was enhanced to achieve improved sampling and control of the solute concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important feature of the SILCS methodology is the use of GCMC sampling allowing for improved sampling of water and solutes throughout the simulation systems over that, which can occur versus the use of MD alone along with the ability to sample very deep and fully occluded pockets on the interior of proteins. To further improve the GCMC acceptance rates for solutes, we previously developed the oscillating μ ex GCMC approach, 8 which has been used successfully in a number of studies 43 . Accordingly, taking advantage of the improved sampling and computational efficiency associated with the GPU implementation described above, the oscillating μ ex GCMC methodology was enhanced to achieve improved sampling and control of the solute concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…( for solutes, we previously developed the oscillating μ ex GCMC approach, 8 which has been used successfully in a number of studies. 43 Accordingly, taking advantage of the improved sampling and computational efficiency associated with the GPU implementation described above, the oscillating μ ex GCMC methodology was enhanced to achieve improved sampling and control of the solute concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Literatures note that drugs to inhibit COX-2 enzyme have the potency to promote cardiovascular side effects [5,6]. An approach to explore cardiotoxicity is through hERG potassium channel, which plays an eminent role in cardiac function, conducting electrical activity in the heart [23,24]. If the inhibition hERG channel occurs, it can cause QT (a measured time of a cycle in cardiogram between wave Q and wave T) interval prolongation, which can increase cardiac arrhythmias or torsades de pointes (TDP) [25].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we proposed a new class of similarity indices: extended similarity indices [17][18][19], that allow comparing any number of molecules at the same time, with a much more attractive O(N) scaling. These new measures have been successfully applied in clustering tasks [20], studying phylogenetic trees [19], epigeneticfocused libraries [21], in feature selection [22], sampling of molecular dynamics simulations [23], and many other studies [24][25][26][27]. More notably, it has been shown that these indices can provide a very efficient way to quantify the chemical diversity of large libraries [28].…”
mentioning
confidence: 99%